Investigation of the Chemomarkers Correlated with Flower Colour in Different Organs of Catharanthus roseus Using NMR‐based Metabolomics. Issue 1 (21st October 2013) - Pan, Qifang; Dai, Yuntao; Nuringtyas, Tri Rini; Mustafa, Natali Rianika; Schulte, Anna Elisabeth; Verpoorte, Robert; Choi, Young Hae
ABSTRACT Introduction Flower colour is a complex phenomenon that involves a wide range of secondary metabolites of flowers, for example phenolics and carotenoids as well as co‐pigments. Biosynthesis of these metabolites, though, occurs through complicated pathways in many other plant organs. The analysis of the metabolic profile of leaves, stems and roots, for example, therefore may allow the identification of chemomarkers related to the final expression of flower colour. Objective To investigate the metabolic profile of leaves, stems, roots and flowers of Catharanthus roseus and the possible correlation with four flower colours (orange, pink, purple and red). Methods 1H‐NMR and multivariate data analysis were used to characterise the metabolites in the organs. Results The results showed that flower colour is characterised by a special pattern of metabolites such as anthocyanins, flavonoids, organic acids and sugars. The leaves, stems and roots also exhibit differences in their metabolic profiles according to the flower colour. Plants with orange flowers featured a relatively high level of kaempferol analogues in all organs except roots. Red‐flowered plants showed a high level of malic acid, fumaric acid and asparagine in both flowers and leaves, and purple and pink flowering plants exhibited high levels of sucrose, glucose and 2, 3‐dihydroxy benzoic acid. High concentrations of quercetin analogues were detected in flowers and leaves of purple‐flowered plants. Conclusions There is a correlation between the metabolites specifically associated to the expression of different flower colours and the metabolite profile of other plant organs and it is therefore possible to predict the flower colours by detecting specific metabolites in leaves, stems or roots. This may have interesting application in the plant breeding industry. Copyright © 2013 John Wiley & Sons, Ltd.